The effect of relative advantage and e-wom on consumer attitudes in online shopping mediated by trust - Febry Elbi Saputra; Sefni Novita Sari; Susi Evanita (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the effect of relative advantage and Electronic Word of Mouth (E-WOM) on consumer attitudes in online shopping with trust as a mediating variable. Given the rapid growth of e-commerce in Indonesia, understanding the factors that shape consumer trust and purchasing decisions is crucial for businesses and policymakers. This study uses a quantitative approach with a descriptive survey method. Data was collected through an online questionnaire from 114 respondents selected using the purposive sampling technique. The research model was analyzed using Structural Equation Modeling (SEM) with SmartPLS 4 to test the direct relationship and mediation between variables. The results show that relative advantage and E-WOM have a positive and significant effect on consumer trust, which in turn affects their attitude towards online shopping. The role of trust mediation strengthens the relationship between these factors and consumer attitudes, emphasizing that trust is the main determinant in shaping consumers' positive perceptions of e-commerce transactions. The implications of the findings of this study provide theoretical insights into the mechanism of consumer trust in e-commerce as well as practical recommendations for businesses to improve product advantage and manage customer reviews effectively. In addition, policymakers are encouraged to implement stricter regulations related to transaction security, data protection, and consumer rights to create a more trusted digital market ecosystem. Further research is suggested to expand the scope of demographics and add other variables, such as risk perception and user experience, to gain a more comprehensive understanding of consumer behavior in e-commerce.